2012
DOI: 10.1016/j.chemgeo.2011.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Unifying natural and laboratory chemical weathering with interfacial dissolution–reprecipitation: A study based on the nanometer-scale chemistry of fluid–silicate interfaces

Abstract: in particular the leached layer theory. Most importantly, our data provide critical evidence for 51 a single mechanism based on interfacial dissolution-reprecipitation. This concept not only 52 unifies weathering processes for the first time, but we also suggest that nanoscale-surface 53 processes can have a potentially negative impact on CO 2 uptake associated with chemical 54 weathering. The results in this study, when combined with recently published research on 55 fluid-assisted mineral replacement reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

22
266
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 261 publications
(290 citation statements)
references
References 92 publications
22
266
0
2
Order By: Relevance
“…We suggest that the nano-scale observations of the quartz -white mica phase boundaries show direct evidence for operation of island-and-channel model as described in Wassmann and Stöckhert (2013), while K-feldspar -quartz phase boundaries represents amorphous layers formed via interface-coupled dissolution-reprecipitation as described by Hellmann et al (2012). …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…We suggest that the nano-scale observations of the quartz -white mica phase boundaries show direct evidence for operation of island-and-channel model as described in Wassmann and Stöckhert (2013), while K-feldspar -quartz phase boundaries represents amorphous layers formed via interface-coupled dissolution-reprecipitation as described by Hellmann et al (2012). …”
Section: Introductionmentioning
confidence: 99%
“…Although there is number of papers focusing on pressure solution and dissolution-precipitation, we will mainly discuss the models of Wassmann and Stöckhert (2013) and Hellmann et al (2012) for which we found direct evidence in our natural samples.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3] The environmental implications of mineral surface chemistry are manifold and diverse. They include atmospheric CO 2 drawdown associated with silicate mineral dissolution, [4,5] removal from solution of adsorptive metal and oxyanion contaminants, [6] nutrient retention for plant growth [7] and organic matter stabilisation against microbial biodegradation. [8] Through a combination of macroscopic experiments, molecular spectroscopy studies, and molecular modelling, environmental chemists are developing an improved understanding of the molecular-scale controls over the rates and extents of mineral surface reactions.…”
mentioning
confidence: 99%